The Rise of Native Self-determination and the Crisis of the Canadian Political Regime - Tolvanen, Ahti (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1992)
This first commentary is part of a larger study which the author is doing at Abo Akademi, on minority communities and the right to development, using case examples from various societies. It presents an intriguing view from an outside commentator on some aspects of Native politics in Canada. In this paper, the author attempts to discuss how a marginalized people are exploiting a historical moment of national crisis to overcome repressed status. In Canada this end is being achieved by the emerging movement for Native rights.